Projek Penguatan Profil Pelajar Pancasila untuk Menanamkan Nilai Karakter Mandiri Sejak Dini pada Anak Di RA Masyithoh III Ropoh - Saputri , Anisa (Literasi: Jurnal Pendidikan Guru Indonesia, 2024)
This research aims to: (1) To find out the principles of the project to strengthen the profile of Pancasila students at RA Masyithoh III Ropoh (2) To find out the activities of instilling independent character values from an early age in children at RA Masyithoh III Ropoh (3) To find out the habits carried out in the project to strengthen student profiles Pancasila at RA Masyithoh III Ropoh to instill independent character values from an early age in children. This type of research uses qualitative research. Data collection techniques use interview, observation, documentation methods after the data is collected and analyzed using data collection, data reduction, data presentation and conclusions.Based on this research, it can be concluded that (1) Implementation of the Pancasila Student Profile Strengthening Project to instill independent character values in children from an early age at RA Masyithoh III Ropoh. (2) Teacher efforts and results in forming independent character through the Project for Strengthening Pancasila Student Profiles at RA Masyithoh III Ropoh. (3) Supporting and inhibiting factors in the implementation of the Pancasila Student Profile Strengthening Project to instill independent character values in children at RA Masyithoh III Ropoh.